Effect of echo‐sampling strategy on the accuracy of out‐of‐phase and in‐phase multiecho gradient‐Echo MRI hepatic fat fraction estimation. Issue 3 (29th May 2013) - Levin, Yakir S.; Yokoo, Takeshi; Wolfson, Tanya; Gamst, Anthony C.; Collins, Julie; Achmad, Emil A.; Hamilton, Gavin; Middleton, Michael S.; Loomba, Rohit; Sirlin, Claude B.
Abstract : Purpose: To assess the effect of echo‐sampling strategy on the accuracy of out‐of‐phase (OP) and in‐phase (IP) multiecho gradient‐echo magnetic resonance imaging (MRI) hepatic fat fraction (FF) estimation, using MR spectroscopy (MRS) proton density FF (PDFF) as a reference standard. Materials and Methods: In this Institutional Review Board (IRB)‐approved, Health Insurance Portability and Accountability Act (HIPAA)‐compliant prospective study, 84 subjects underwent proton MRS and non‐T1 ‐weighted gradient‐echo imaging of the liver at 3T. Imaging data were collected at 16 nominally OP and IP echo times (TEs). MRI‐FF was estimated while varying two echo‐sampling parameters (number of consecutive echoes, starting echo number). For each combination of these parameters, MRI‐FF estimation accuracy was assessed with slope, intercept, average bias, and R 2 from a linear regression of MRS‐PDFF on MRI‐FF. The relationship between accuracy metrics and echo‐sampling parameters was assessed by Spearman rank correlation. Results: For FF calculations using 3–16 echoes and a starting echo number of 1, the intercept ranged from 0.0046 to 0.0124, slope from 0.941 to 0.96, average bias from 0.0034 to 0.0078, and R 2 from 0.968 to 0.976. All four accuracy metrics were the best with the 3‐ and 4‐echo calculations and worsened progressively with an increasing number of echoes. For a given number of echoes, there was an overall trend toward decreasing accuracy as starting echo number increased. Spearman correlation coefficients between starting echo number and intercept, slope, average bias, and R 2 were 0.911, −0.64, −0.889, and −0.954, respectively, indicating progressive loss of accuracy in each case. Conclusion: Multiecho OP and IP imaging provided high FF estimation accuracy. Accuracy was highest using the earliest 3 or 4 echoes. Incorporation of additional echoes or delaying the starting echo number progressively reduced accuracy.J. Magn. Reson. Imaging 2014;39:567–575 . ©2013 Wiley Periodicals, Inc.